Shared genetic architecture between the two neurodegenerative diseases: Alzheimer’s disease and glaucoma - Zheng, Chunwen; Liu, Shunming; Zhang, Xiayin; Hu, Yunyan; Shang, Xianwen; Zhu, Zhuoting; Huang, Yu; Wu, Guanrong; Xiao, Yu; Du, Zijing; Liang, Yingying; Chen, Daiyu; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Considered the representatives of neurodegenerative diseases, Alzheimer’s disease and glaucoma are complicated progressive neuropathies affected by both genetic and environmental risk factors and bring irreversible damages. Current research indicates that there are common features between Alzheimer’s disease and glaucoma on epidemiology and pathophysiology. However, there are still limited understandings and insufficient explanations of their comorbidity and potential genetic overlaps. Method: Genetic pleiotropy analysis was performed using large genome-wide association studies summary statistics of Alzheimer’s diseases and glaucoma, with an independent cohort of glaucoma for replication. Conditional and conjunctional false discovery rate methods were applied to find the shared loci. Biological function and network analysis as well as the expression level analysis were performed to investigate the significance of the shared genes. Results: A significantly positive genetic correlation between Alzheimer’s disease and glaucoma was identified, indicating that there are significant polygenetic overlaps. Forty-nine shared loci were found and mapped onto 11 shared protein-coding genes. The functional genomic analyses of the shared genes indicate their modulation of some critical physiological processes of human cells, including those occurring in mitochondria, nucleus, and cellular membranes. Most of the shared genes indicated a potential modulation of metabolic processes in human cells and tissues. Human protein-protein interaction network analyses found that some of the shared genes, especially MTCH2, NDUFS3, and PTPMT1, as well as SPI1 and MYBPC3, may function concordantly. Modulation of their expressions might be related to metabolic dysfunction and pathogenic processes. Conclusions: Our study identifies shared genetic architecture between Alzheimer’s disease and glaucoma, which may explain their shared features in epidemiology and pathophysiology. The potential involvement of these shared genes in the molecular and cellular processes reflects the “Inter-Organ Crosstalk” between Alzheimer’s disease and glaucoma. These results may serve as a genetic basis and inspiration for the development of innovative and effective therapeutics for Alzheimer’s disease and glaucoma, as well as other neurodegenerative diseases.